Arterial spin labelling reveals multi-regional cerebral hypoperfusion in patients with transient ischemic attack that are unrelated to ischemia location: A proof-of-concept study - Meaghan Reid; George S. Tadros; Connor C. McDougall; Noaah Reaume; Brooklyn McDougall; Rani Gupta Sah; Meng Wang; Eric E. Smith; Richard Frayne; Shelagh B. Coutts; Tolulope Sajobi; R. Stewart Longman; et al. (Cerebral Circulation - Cognition and Behavior, 2023)
Background and Aims: Patients with transient ischemic attack (TIA) have a substantially increased risk of early dementia. In this exploratory study, we aim to determine whether patients with TIA have 1) measurable regional cerebral hypoperfusion unrelated to the location of ischemia, and 2) determine the relationship of regional cerebral blood flow (rCBF) with their cognitive profiles. Methods: Patients with TIA (N = 49) and seventy-nine (N = 79) age and sex matched controls underwent formal neuropsychological testing and MRI. Quantitative arterial spin labelling rCBF maps (mL/min/100 g) were registered to the corresponding high resolution T1-weighted image. Linear regression was used to determine the association between demographic, clinical and cognitive variables and rCBF. Results: Patients with TIA had significantly (p < 0.05) lower cognitive scores in the MMSE, MOCA, ACE-R, WAIS-IV DS Coding and Trail Making Tests A and B compared to controls. TIA patients had significantly lower rCBF in the left entorhinal cortex (p = 0.03), right posterior cingulate (p = 0.04), and right precuneus (p = 0.05), after adjusting for age and sex, that were unrelated to the regional anatomical volume and DWI positivity. Regional hypoperfusion in the right posterior cingulate and right precuneus was associated with impaired visual memory (BVMT total, p = 0.05 for both regions) and slower processing speed (TMT A, p = 0.04 and p = 0.01), respectively after adjusting for age and sex. Conclusions: TIA patients have patterns of regional hypoperfusion in multiple cortical regions unrelated to the parcellated regional anatomical volume or the presence of a DWI lesion. Regional hypoperfusion in patients with TIA may be an early marker conferring risk of future cognitive decline that needs to be confirmed by future studies.